Transformation of the Genre of Still Life in Painting and Literature - Kharlan, Olha; Shkola, Iryna; Saliuk, Bohdana; Bohdanova, Maryna; Melnikova, Yuliia (Journal of History Culture and Art Research, 2020)
The article deals with one of the urgent problems of modern literature genealogy – the transformation of genres, which is quite significant especially within the context of intermedial interaction between two arts – literature and painting. The transformation of the genre of still life, starting with painting and continuing in literature, is in the focus of the current scientific research. It is mentioned that the evolution of still life painting from flower framing Madonna in the 15th – 16th centuries, through raising in the works of Dutch and Flemish artists in the 17th– 18th centuries, till Impressionism view on depicting the objects has been changing the understanding of the term itself. The diversity of the meaning of still life as a term of painting genre was caused by different interpretations of the Dutch term “stilleven” in national arts and artistic epochs. This issue is also important to discover whereas to understand the author’s interpretation of a literary work through the use of the term “still life” it is necessary to refer to its origin. Transformed into literary genre still life became verbal and acquired several meanings – actually ekphrasis (description of a still life art canvas); hypothyroidism (verbal still life); the use takes place at the level of the nomenosphere (playing in the titles of works of the term “dead life”) – that are analyzed on the basis of stories (“Still Life with Cats” by Vasyl Trubay, “Military Flyer” by V. Pidmohylny), crime stories (“Still Life with Woodpecker” by T. Robbins, “Still Life with Crows” by D. Preston and L. Child and in “Still Life” by Joy Fielding), novel (“Rösleinrot” by I. Noll). It is emphasized that in literary still life objects become a kind of subject of action, which is in a system of new relationships, whereas it is important not only to depict things in the text, but also to show how they coexist (composition) and how to depict the space where their relationship takes place.
Keywords: Intermediality; still life; genre; painting; literature